2020
DOI: 10.1007/s00127-020-01836-6
|View full text |Cite
|
Sign up to set email alerts
|

How service users and carers understand, perceive, rephrase, and communicate about “depressive episode” and “schizophrenia” diagnoses: an international participatory research

Abstract: Background For ICD-11, the WHO emphasized the clinical utility of communication and the need to involve service users and carers in the revision process. Aims The objective was to assess whether medical vocabulary was accessible, which kinds of feelings it activated, whether and how users and carers would like to rephrase terms, and whether they used diagnosis to talk about mental health experiences. Method An innovative protocol focused on two diagnoses (depressive episode and schizophrenia) was implemented i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 20 publications
0
18
0
1
Order By: Relevance
“…One participant noted that the term is "very negative" and that this negativity is "… due to (the word) delusion and due to the emotional potency these words bear, the guilt, and the interconnection of all these…" Nevertheless, only 60% of Greek participants reported that the term 'persistent delusions' matched a present or past experience (less than international rates) and only 40% stated that they would propose a rephrasing of the term (signi cantly less than the international average). Equally, for the term 'persistent hallucinations', Greek participants reported higher rates of understanding than the international average (86,6% vs. 75,6%), with the term being associated with something negative for 80% of the sample (again signi cantly higher than the international average) (Roelandt et al, 2020). Seventy three percent of Greek service users, one of the highest internationally, stated that they would suggest a rephrasing for the term 'persistent hallucinations' since 60% of the national sample reported that the term matched a current or past experience.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…One participant noted that the term is "very negative" and that this negativity is "… due to (the word) delusion and due to the emotional potency these words bear, the guilt, and the interconnection of all these…" Nevertheless, only 60% of Greek participants reported that the term 'persistent delusions' matched a present or past experience (less than international rates) and only 40% stated that they would propose a rephrasing of the term (signi cantly less than the international average). Equally, for the term 'persistent hallucinations', Greek participants reported higher rates of understanding than the international average (86,6% vs. 75,6%), with the term being associated with something negative for 80% of the sample (again signi cantly higher than the international average) (Roelandt et al, 2020). Seventy three percent of Greek service users, one of the highest internationally, stated that they would suggest a rephrasing for the term 'persistent hallucinations' since 60% of the national sample reported that the term matched a current or past experience.…”
Section: Discussionmentioning
confidence: 90%
“…Sixty-six percent (66,7%) of Greek participants reported that they would rephrase the term 'schizophrenia, which is the highest rate along with that of Hungary. The average international rate for rephrasing was 42,7%, with the lowest being reported in India (6,8%) and Mauritania (13,3%) (Roelandt et al, 2020). The high rates represented by the Greek sample may re ect the emotional impact that psychiatric language has, with the term 'schizophrenia', meaning split-mind in Greek, inducing the intended distress in its primary form, compared to other languages whereby the understanding of the term follows a top-down rather than a bottom-up process.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…We also question (Q3) how these potentials can be impacted by the COVID-19 pandemic and (Q4) how the lived experience of people in recovery can be mobilized to cope with the situation. Finally, we also explore (Q5) how sex and gender considerations can be taken into account for the pairing of PSWs with service users beyond considerations based solely on psychiatric diagnoses or specific MHPIs [35]. We aim to collect data for a future randomized controlled trial (RCT) [36] by clarifying a certain number of remaining uncertainties and by detecting an effect that would be specifically attributable to transitional peer support as facilitated by trained PSWs.…”
Section: Principal Research Questionsmentioning
confidence: 99%